Assessing Customer Satisfaction in AI-Powered Services: An Empirical Study with SmartPLS - Achani Rahmania Az Zahra; Dendy Jonas; Ita Erliyani; Rosdiana; Natasya Aprila Yusuf (Pandawan Sejahtera Indonesia, 2023)
In the contemporary business landscape, the evaluation of customer satisfaction plays a pivotal role in assessing the effectiveness of AI-powered services. This empirical study, bolstered by the robust analytical tool, SmartPLS, systematically scrutinizes the intricate relationship between AI-powered services and customer satisfaction. With a rigorous and methodical service quality analysis, conducted with a sample of 189 respondents, we unveil the salient attributes and determinants that underpin customer satisfaction within the framework of AI-driven services. This research contributes substantially to a more profound comprehension of how organizations can strategically enhance customer satisfaction via the adept deployment of AI technologies. The ensuing findings, derived from the comprehensive analysis of 189 respondents, provide invaluable insights into the optimization of service quality within AI-powered ecosystems. These insights hold the potential to cultivate heightened levels of customer satisfaction and engender enduring loyalty, which is of paramount importance in the contemporary business landscape.